Short pulse generations in 1.0 and 1.5 micron regions WITH AuNP and MXene TI3C2TX saturable Absorbers / Ahmad Haziq Aiman Rosol - Ahmad Haziq , Aiman Rosol (2021)
Q-switched and mode-locked fiber lasers have gained the attention of researchers due to their extensive applications in various fields including telecommunication, material processing, remote sensing and medical. These lasers are normally realized by using a saturable absorber (SA), which functions to initiate pulses by passive means. Up to date, many works have been devoted to developing new SA devices which have good optical stability and can produce high performance pulse lasers. This thesis aimed to explore the use of gold nanoparticles (AuNPs) and MXene Ti3C2Tx as SA device for Q-switched and mode-locked pulse generations in both Erbium-doped fiber laser (EDFL) and Neodymium-doped fiber laser (NDFL) cavities. Using the two materials, four SAs are prepared by employing two different techniques: liquid and film. The AuNPs were synthesized using gold (III) chloride trihydrate (50% Au basis) (HAuCl4), tri–sodium citrate (Na3C6H5O7, TSC), poly(sodium 4-styrenesulfonate) (PSSS), and sodium borohydrate (NaBH4) while the MXene Ti3C2Tx was prepared from MAX Ti3AlC2 based on selective etching technique. It is found that AuNP liquid and film exhibit the modulation depth of 5.6% and 13.6 %, respectively while MXene Ti3C2Tx liquid- and film-based SAs have modulation depth in a range of 4 - 6 %. Q-switched and mode-locked pulses have been successfully demonstrated using the newly developed AuNPs SA devices. For instance, an AuNPs liquid based SA was successfully used in the EDFL cavity to generate Q-switched pulses operating at 1563 nm with the maximum repetition rate of 107 kHz, a minimum pulse width of 1.38 μs and the maximum pulse energy of 100 nJ. The generation of mode-locked pulses operating at 1563 nm was also realized in an extended EDFL cavity based on the plasmonic effect induced by AuNPs film. The laser operated at 1563 nm with a pulse width of 2.85 ps, repetition rate of 0.99 MHz and maximum peak power of 9 kW. Q-switched and mode-locked pulses trains were also demonstrated using two types of newly developed MXene Ti3C2Tx based SAs. For instance, a soliton pulse train operating at 1562.5 nm was produced with a fundamental repetition rate of 1.89 MHz and pulse duration of 3.68 ps using the MXene Ti3C2Txfilm as SA. The mode-locked laser generated average output power of 24.42 mW, pulse energy of 12.92 nJ and peak power of 3.5kW at 144 mW pump power. The result indicates that both AuNPs and MXene Ti3C32Tx have a good nonlinearity and thus are suitable for use in various photonic devices operating in both 1.0 and 1.5 μm regions.